The model developed for stress-induced structural phase transformations of micro-crystalline silicon films - Han, Chang-Fu; Lin, Jen-Fin (Nano-Micro Letters, 2010)
The nanoindentations were applied to island-shaped regions with metal-induced Si crystallizations. The experimental stress-strain relationship is obtained from the load-depth profile in order to investigate the critical stresses arising at various phase transitions. The stress and strain values at various indentation depths are applied to determine the Gibbs free energy at various phases. The intersections of the Gibbs free energy lines are used to determine the possible paths of phase transitions arising at various indentation depths. All the critical contact stresses corresponding to the various phase transitions at four annealing temperatures were found to be consistent with the experimental results.